Nekatere didaktičnometodične značilnosti pouka v šolah na dvojezičnih območjih ob slovenski meji - Javornik Krečič, Marija; Konečnik Kotnik, Eva (Revija za elementarno izobraževanje, 2011)
Some didactic methodical characteristics of school instruction in bilingual areas along the Slovene border. In this discussion we present some didactical-methodical characteristics of school instruction in bilingual areas along the Slovene border. In the first part of the article we briefly present some contemporary trends in teaching school lessons. In the continuation we present the results of empirical research that was carried out between October and December 2010. The sample included 185 teachers. The main goal of our research was to establish some didactical characteristics of school lessons in bilingual areas along the Slovene border.
Keywords: didactical-methodical characteristics; school lesson models; new learning cultures; bilingual areas; teacher